The effectiveness of written asthma action plan on asthma control and quality of life among paediatric asthmatic patients - Ngah, Najwa Diyana (2017)
Background: Bronchial asthma is a chronic disease affecting worldwide population including children. The goal of paediatric asthma management is to achieve good asthma control for the children to live a healthier life. Objectives: To study the effect of Written Asthma Action Plan (WAAP) on the asthma control and quality of life among paediatric asthmatic patients. Methods: An interventional study was conducted from February to June 2016 involving 120 participants, aged from 6 to 12 years old who had partly controlled and uncontrolled asthma. 61 children were allocated to the intervention group that received WAAP with standard asthma education while 59 children were in control group who were only given standard asthma education. The asthma control and quality of life scored using Asthma Control Questionnaire (ACQ) and Paediatric Asthma Quality of Life Questionnaire (PAQLQ) was assessed at baseline and at three months. Repeated measure analysis of variance (ANOVA) was used to analyse mean score difference of both groups after the intervention. Results: There was a significant improvement in asthma control and quality of life after three months follow up. For the analysis of ACQ, there was no significant difference of mean score for asthma control at baseline in between groups, [F(df)=1.17(1,119), P=0.282]. However, at three months, there was a significant different of mean scorebetween groups, [F(df)=7.32(1,119), P=0.008). The mean score (SD) in the interventional group was 0.96(0.53) and in control group was 1.21(0.49). Time-group interaction analysis using RM ANOVA showed significant different of mean score changes [F(df)=5.03(1,116), P=0.027] where lower mean score was seen in the interventional group indicating better asthma control. For analysis of PAQLQ, there was no significant difference of mean score for quality of life baseline for both groups. Again, there was a significant mean score changes for the quality of life [F(df)=10.9(1,119), P=0.001] at three months follow up where those in interventional group scored mean (SD) score of 6.19 (0.45), and control group was 5.94(0.38). Time-group interaction using RM ANOVA showed significant mean score changes [F(df)=11.55(1,116), P=0.001] where higher score was seen in interventional group indicating better quality of life. Conclusions: Written asthma action plan (WAAP) resulted in greater improvement of asthma control and quality of life among asthmatic children. Thus, it is advocated to be given along with standard asthma education as a part of the management of asthma in children.